2017
DOI: 10.1037/xlm0000351
|View full text |Cite
|
Sign up to set email alerts
|

Basic composition and enriched integration in idiom processing: An EEG study.

Abstract: We investigated the extent to which the literal meanings of the words forming literally-plausible idioms (e.g., break the ice) are semantically composed, and how the idiomatic meaning is integrated in the unfolding sentence representation. Participants read ambiguous idiom strings embedded in highly predictable, literal and idiomatic contexts, while their EEG was recorded. Control sentences only contained the idiom-final word whose cloze values were as high as in literal and idiomatic contexts. Event Related P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 94 publications
(223 reference statements)
12
46
1
Order By: Relevance
“…This is particularly important to idioms since, as we mentioned, processing idioms may be more engaging for the cognitive system than it may appear given the rapidity with which familiar idioms are generally understood. In fact, it has been extensively shown that momentary activation of at least part of the literal meaning of the idiom composing words and retrieval, after idiom identification, of the idiom meaning from semantic memory are both necessary to idiom comprehension (Cacciari et al, 2007 ; Fanari et al, 2010 ; Vespignani et al, 2010 ; Holsinger and Kaiser, 2013 ; Canal et al, 2017 ). How many of the words composing the idiom string are literally processed depends on factors such as idiom predictability, familiarity and contextual information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly important to idioms since, as we mentioned, processing idioms may be more engaging for the cognitive system than it may appear given the rapidity with which familiar idioms are generally understood. In fact, it has been extensively shown that momentary activation of at least part of the literal meaning of the idiom composing words and retrieval, after idiom identification, of the idiom meaning from semantic memory are both necessary to idiom comprehension (Cacciari et al, 2007 ; Fanari et al, 2010 ; Vespignani et al, 2010 ; Holsinger and Kaiser, 2013 ; Canal et al, 2017 ). How many of the words composing the idiom string are literally processed depends on factors such as idiom predictability, familiarity and contextual information.…”
Section: Discussionmentioning
confidence: 99%
“…Since retrieving the idiomatic meaning takes less time than computing the compositional meaning of the string, the idiom meaning becomes available before the literal meaning. In more recent years, evidence against this “Lexical-look up” approach has accumulated (e.g., Cacciari and Tabossi, 1988 ; Titone and Connine, 1994 ; Peterson et al, 2001 ; Tabossi et al, 2005 ; Sprenger et al, 2006 ; Cacciari et al, 2007 ; Libben and Titone, 2008 ; Fanari et al, 2010 ; Vespignani et al, 2010 ; Holsinger and Kaiser, 2013 ; Canal et al, 2017 ) leading to “Non-Lexical Hybrid” models. The Configuration Hypothesis (CH, Cacciari and Tabossi, 1988 ; Tabossi and Zardon, 1993 ; Vespignani et al, 2010 ; Cacciari and Corradini, 2015 ) provided an influential model of how spoken idiom comprehension unfolds in time.…”
Section: Models Of Idiom Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…language. Canal et al (2017) and Rommers et al (2013) found increased gamma power in literal compared to idiomatic contexts. Given the proposed role of gamma for semantic integration (e.g., Hagoort et al, 2004), this might reflect the fact that semantic integration is not required for processing idiomatic expressions to the same degree as it is when processing literal expressions.…”
Section: Idiomatic/ironic Languagementioning
confidence: 95%
“…The process of deriving a figurative interpretation of the sentence will however be reflected in the post-N400 window, either by the P600 or by a sustained anterior negativity (SAN) in about the same time range (~ 500-800 ms). P600 effects have been found with metaphor (Bambini et al 2016a), metonymy (Nieuwland and Van Berkum 2005;Schumacher 2011Schumacher , 2014, and idioms (Canal et al 2017). While the standard interpretation of the P600 as just a marker of syntactic processing has been abandoned, it is quite possible that syntax still plays an indirect role here.…”
Section: Neural Aspectsmentioning
confidence: 99%